Differential Survival of Hyper-Aerotolerant Campylobacter jejuni under Different Gas Conditions - Oh, Euna; McMullen, Lynn M.; Chui, Linda; Jeon, Byeonghwa (Frontiers in Microbiology, 2017)
Campylobacter jejuni accounts for a significant number of foodborne illnesses around the world. C. jejuni is microaerophilic and typically does not survive efficiently in oxygen-rich conditions. We recently reported that hyper-aerotolerant (HAT) C. jejuni are highly prevalent in retail poultry meat. To assess the capabilities of HAT C. jejuni in foodborne transmission and infection, in this study, we investigated the prevalence of virulence genes in HAT C. jejuni and the survival in poultry meat in atmosphere at a refrigeration temperature. When we examined the prevalence of eight virulence genes in 70 C. jejuni strains from raw poultry meat, interestingly, the frequencies of detecting virulence genes were significantly higher in HAT C. jejuni strains than aerosenstive C. jejuni strains. This suggests that HAT C. jejuni would potentially be more pathogenic than aerosensitive C. jejuni. Under aerobic conditions, aerosensitive C. jejuni survived at 4°C in raw poultry meat for three days, whereas HAT C. jejuni survived in poultry meat for a substantially extended time; there was a five-log CFU reduction over two weeks. In addition, we measured the effect of other gas conditions, including N2 and CO2, on the viability of HAT C. jejuni in comparison with aerosensitive and aerotolerant strains. N2 marginally affected the viability of C. jejuni. However, CO2 significantly reduced the viability of C. jejuni both in culture media and poultry meat. Based on the results, modified atmosphere packaging using CO2 may help us to control poultry contamination with HAT C. jejuni.